SPACs : Utilization and performance in the USA - Pospíšil, Štěpán; Houska, Daniel; Tomčiak, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The paper compares SPAC quantitative research papers, reports, infographics, and data sets. The bachelor thesis derives outcomes that should give valuable info not only to involved parties (public investors and target companies) about SPAC profitability, time-efficiency, and cost-effectivity during the years 2010-2021 in the USA. The thesis uses IPOs and direct listings as a benchmark. The work might help readers navigate and filter through the tremendous amount of SPAC headlines, news, and information. Readers should also get a basic overview of how SPACs are organized, the parties involved in SPAC, and their primary interests.
Vedoucí práce: Daniel Houska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses